MlNERALOGICAL STUDY OF Mg-SKARNS WITH CLINOHUMITE AT THE OMERLI SITE AGGISTRO, SERRES - Δήμου, Ε.; Κούκουζας, Κ. (Bulletin of the Geological Society of Greece, 2004)
Mg-skam occurrences located in the dolomitic marbles at the Omerli site near Aggistro are studied. The dolomitic marbles are gradually enriched in metasomatic minerals, up to the full replacement and the formation of cohesive lenticular beds of skarns in the marbles. The aplito-pegmatitic veins traversing the surrounding marbles as well as the granodiorite occurring in the broader area of Ahladohoho, are considered responsible for the phenomena of thermal metamorphism and metasomatism in the dolomites. On the basis of mineralogical analytical methods (optical microscopy, X-Ray diffraction, microanalysis) the following metasomatic minerals in decreasing order, have been determined: Clinohumite (Mg, Fe +)Q (Si04)4(F,OH)2, forsterite Mg2Si04, spinel MgAb04, hornblende-pargasite NaCa2 (MgFe% AI(SÌ6AI2)022(F,OH)2, clinochlore (MgFe2+)AI(SÌ3AI)Oi0(OH)8, phlogopite KMg3SÌ3AIOio(F, OH)2, dolomite, calcite. The mineral chemistry and petrography of the above assemblages lead to the conclusion that the skarns at Omerli site constitute pure metasomatic concentrations at the expense of the dolomites, with addition of elements from external thermal source and removal of elements from the hosting dolomites. It is, therefore, an open chemical system and not an iso-chemical one.